Redefining Emergency Services with Generative AI: Insights from a preliminary literature review - Kröckel, Pavlina (Proceedings of the 15th International Conference on Applied Human Factors and Ergonomics (AHFE 2024), 2024)
The rapid evolution of artificial intelligence (AI) technologies, particularly generative AI (GenAI), has opened new frontiers in various sectors including emergency services. We present the results of a preliminary literature review of the current research on generative AI in emergency departments with a focus on use cases and their implications. We systematically examine peer-reviewed articles, case studies, and practical implementations to identify key trends, challenges, and opportunities in this growing field. Our findings underscore the need for ongoing research, ethical considerations, and cross-sector collaboration to fully leverage AI's capabilities to enhance the effectiveness and efficiency of emergency response.
Keywords: GenAI; ChatGPT; Triage; Emergency; SLR; LLM